Aesthetics of Metaphorical Imagery in the Elegies of Sharif Razi - Narges Ansari; Alireza Nazari (دراسات في اللغة العربيّة وآدابها)
Imagery has been an important subject among the men of literature and dealing with this issue is not considered an extraordinary matter. This literary device plays a prominent role in transmitting the poet's feelings and experiences to its addressees. Employing various styles of imagery by the poet provides the reader with rather a detailed and clearer literary work. This phenomenon is highlighted in the works of a great poet, Sharif Razi, of the Abbasid dynasty. With the help of imagery in drawing a canvas of concepts and themes, Razi aimed to emphasize his literary style on the reader. In relation to different poetic imageries, the present paper endeavors to investigate the metaphorical imagery in the elegies of this poet. In this regard, before analyzing the poems, a brief introduction on the practical aspects of this kind of imagery is provided. More than eighty odes and elegies of the aforementioned poet has been studied, its metaphorical imageries have been extracted, and thematically categorized. These themes mostly deal with the condition of the diseased person, the mourners, the mental state of the poet, death, time and tragedy. Moreover, the proportion of the images in relation to the represented themes is also taken into account. Onomotopia, colors along with their inspirational concepts are the result of this study. Furthermore, materialistic and concrete elements are the predominant features of the used imageries in which the poet has been inspired by nature and reality.